2008
DOI: 10.4137/bmi.s595
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Arrays Identify Potential Diagnostic Markers of Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the third leading cause of cancer deaths worldwide. Effective treatment of HCC patients is hampered by the lack of sensitive and specifi c diagnostic markers of HCC. Alpha-fetoprotein (AFP), the currently used HCC marker, misses 30%-50% of HCC patients, who therefore remain undiagnosed and untreated. In order to identify novel diagnostic markers that can be used individually or in combination with AFP, we used an antibody array platform to detect the levels of candidate protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…similarly, the serum levels of β-catenin were also higher in patients with CH than in AsC patients and healthy controls. these data are in agreement with previous reports by sun et al (20), where higher serum level of β-catenin were measured in patients with HCC compared with those in CH patients. the authors of this study suggested that serum level of β-catenin could be used clinically to complement the current AFp diagnostic test for more accurate detection of early HCC.…”
Section: Serum Levels Of E-cadherin Icam-1 Mmp-2 Vegf Opnsupporting
confidence: 83%
“…similarly, the serum levels of β-catenin were also higher in patients with CH than in AsC patients and healthy controls. these data are in agreement with previous reports by sun et al (20), where higher serum level of β-catenin were measured in patients with HCC compared with those in CH patients. the authors of this study suggested that serum level of β-catenin could be used clinically to complement the current AFp diagnostic test for more accurate detection of early HCC.…”
Section: Serum Levels Of E-cadherin Icam-1 Mmp-2 Vegf Opnsupporting
confidence: 83%
“…Our result indicated that it is possible to detect cancer-specific expression patterns using antisense transcripts. In this study, we also investigated the profile of sense transcripts, and expression changes in the gene, DPT (39), CXCL14 (40), HAMP (41), MAGE1A (42) were consistent with results of previous studies. In contrast to genes discussed above, some genes that were reported previously were not recognized in the present study.…”
Section: Discussionsupporting
confidence: 73%
“…Levels were lower in women with breast cancer [92], prostate cancer [93], and hepatocellular cancer [94] than in those with benign diseases of the same organ. However, two studies of women with ovarian cancer showed discrepant results [95,96].…”
Section: Circulating Levelsmentioning
confidence: 84%